The Decision To Borrow From “Bank Thithil” (Case In The Society of Kopeng Village, Semarang Regency) - ., Rusdarti; Sakitri, Wijang; Septiani, Ika (KnE Social Sciences, 2019)
The paper aims to describe the proﬁle of bank thithil’s customers and the bank thithils themselves. It also aims to analyze the motives, the causes of the decision to borrow money from bank thithils repeatedly, and the role of social capitals in the decision to borrow money from bank thithils. The method used in the research is qualitative research with open interviews. The mechanical determination with informants criteria by the researcher is tested by triangulation. The data are analyzed using interactive models of Miles and Huberman. The research shows that 36.36% of bank thithil customers are small-sized traders, 54.55% hotel labors, and 9.09% inn owners. Bank thithils are not Kopeng villagers. The non-economic motives include attractedness to bank thithil’s loan. The factors that cause the loan in bank thithil to last repeatedly are: consumptive characteristic of the people, bank thithil’s agressiveness, and provision of new loans when the customer fails to repay their debts. The role of social capitals are very strong in the decision made to borrow some money from bank thithils. These social capitals act as an adhesive, bridges, and lubricants of bank thithil loan bussines. Social capitals have given negative impacts on society in a longer term because these make it harder for the people in Kopeng village to set themselves free from debts in the bank thithils. Keywords: Bank thithil, Credit, Motive, Social Capital